PENGARUH MODAL USAHA DAN PERMINTAAN PASAR TERHADAP PENDAPATAN USAHA KULINER BAKSO DI KECAMATAN SAWAHAN KOTA SURABAYA - Salsabilla Saifana Veriyanto; Arga Christian Sitohang (Nirta Learning Centre, 2025)
This study employs a quantitative approach using multiple linear regression analysis. This method is applied to assess the extent to which the two independent variables—business capital (X1) and market demand (X2)—influence the dependent variable, business revenue (Y). Primary data were obtained through questionnaires distributed to the entire population, which also served as the sample (census), consisting of 30 meatball vendors in Sawahan District, Surabaya City. The primary aim of this research is to evaluate how strongly capital and market demand contribute to determining the income level of meatball culinary businesses. The results of the analysis indicate that, jointly, business capital (X1) and market demand (X2) significantly affect revenue, as reflected by an R² value of 68%. However, based on partial testing, only market demand (X2) shows a significant influence, while business capital (X1) does not demonstrate a significant individual effect. These findings highlight the dominant role of market demand in increasing revenue, whereas effective managerial practices are essential for optimizing the impact of capital. For business owners, the ability to respond to market shifts and manage capital efficiently is crucial for sustaining their operations. It is expected that these results will serve as both an academic reference and a practical guideline for the advancement of local culinary enterprises.